2014
DOI: 10.1021/ac501436d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarapid Detection of Pathogenic Bacteria Using a 3D Immunomagnetic Flow Assay

Abstract: We developed a novel 3D immunomagnetic flow assay for the rapid detection of pathogenic bacteria in a large-volume food sample. Antibody-functionalized magnetic nanoparticle clusters (AbMNCs) were magnetically immobilized on the surfaces of a 3D-printed cylindrical microchannel. The injection of a Salmonella-spiked sample solution into the microchannel produced instant binding between the AbMNCs and the Salmonella bacteria due to their efficient collisions. Nearly perfect capture of the AbMNCs and AbMNCs-Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 15 publications
0
69
0
Order By: Relevance
“…Since its invention in the late 1980s, 3D printing offers the opportunity for manufacturers to circumvent the time-consuming steps of traditional manufacturing technology via a full-scale or scaled-down mechanical replica of the products designed by computers [46][47][48][49]. A broad range of research components, including chemical reaction-ware [40,44,48,50], gradient generators [51,52], instrumental setups and interfaces [53][54][55][56][57], droplet extractors [52], and user-oriented functional devices [58][59][60][61] have been successfully built with the aid of 3D printing technologies confirming the feasibility of this approach. Further modification of 3D printed devices via adding chemicals or precursors of interest or post-printing surface functionalization extend the applicability of constructed products [45,62,63].…”
Section: D Printing Technologiesmentioning
confidence: 99%
“…Since its invention in the late 1980s, 3D printing offers the opportunity for manufacturers to circumvent the time-consuming steps of traditional manufacturing technology via a full-scale or scaled-down mechanical replica of the products designed by computers [46][47][48][49]. A broad range of research components, including chemical reaction-ware [40,44,48,50], gradient generators [51,52], instrumental setups and interfaces [53][54][55][56][57], droplet extractors [52], and user-oriented functional devices [58][59][60][61] have been successfully built with the aid of 3D printing technologies confirming the feasibility of this approach. Further modification of 3D printed devices via adding chemicals or precursors of interest or post-printing surface functionalization extend the applicability of constructed products [45,62,63].…”
Section: D Printing Technologiesmentioning
confidence: 99%
“…Lee et al [90] developed a novel 3D immunomagnetic flow assay for the rapid detection of pathogenic bacteria in a large-volume food sample ( Figure 4(a)). Antibody-modified magnetic nanoparticle clusters (AbMNCs) were immobilized on the surface of a 3D-printed cylindrical microchannel by an external applied magnetic field.…”
Section: Magnetic Manipulationmentioning
confidence: 99%
“…(a) Schematic illustrations of 3D immunomagnetic flow assay[90]; (b) schematic illustration of the multiplexed electrochemical immunoassay protocol and the measurement principles of the sandwich immunoassay[95]; (c) schematic of LAM with thrombin as the analyte and dose-response curve for the detection of thrombin by LAM[96].…”
mentioning
confidence: 99%
“…Most recently, we have demonstrated that a 3D-printed µFD (3DpμFD) is an excellent platform for detecting pathogens because of its high speed, integration, and automation [17] Compared to photolithography and soft lithography, 3D printing has many advantages when printing μFDs because this technique easily enables printing high aspect ratio structures and does not require complex binding steps to form a monolithic structure. In recent years, considerable efforts have been devoted to the development of 3D printing microfluidic platforms for separation and detection [17][18][19]. However, to the best of our knowledge, there have been no reports showing that both IMS and DNA purification functions were integrated into a single device.…”
Section: Introductionmentioning
confidence: 99%